Leaving a Bequest: Living on Through Charitable Gifts. (October 2015) - Routley, Claire; Sargeant, Adrian
Decisions taken in respect of the disposition of possessions often parallel a life transition or change in identity. In this article, we examine decisions taken in a will where disposition can be viewed not as a representation of the identities an individual wishes to shed, but rather as the continuation of those for which the deceased wishes to be remembered. We examine the meaning that such donors ascribe to their giving and the rich pattern of utility it offers both the individual and those he or she will ultimately leave behind. Using grounded theory, we report the results of 20 in-depth interviews conducted with individuals who had pledged a bequest to at least one U.K. charity. We demonstrate how the bequest gift is laden with symbolism, a function of the reminiscences of the individual and reflective of the need for the self to live on and achieve a degree of symbolic immortality.